Analisis Administrsi Keuangan Sekolah di Era Society 5.0 - Astri Sukriani Piliang; Izatul Hasanah; Ahmad Sabri; Rully Hidayatullah (Pusat Riset dan Inovasi Nasional, 2025)
Financial administration is the process of managing financial resources in an organization or institution. This includes planning, controlling and making decisions regarding the acquisition and use of funds to achieve organizational goals effectively and efficiently. The emergence of information technology is poised to revolutionize the field of education. With the increasingly rapid development of technology, the role of management information systems in maintaining school competitiveness has become very important. To adapt to the demands of Industry 5.0, educational institutions must use portable application-based management information systems to simplify data management. Principals, teachers, students and parents, the system can be customized to meet the unique needs of each school, increase school engagement, and better prepare students for a computer-based world. School financial administration is not only about managing money, but also about ensuring that financial resources support the school's vision, mission and programs in improving the quality of education. This abstract discusses how to manage and organize school finances effectively in educational activities. This research aims to analyze and understand how to overcome financial problems in schools. Overall, school financial administration in the Society 5.0 era must focus on efficient management of funding sources and transparent accountability. Schools need to utilize technology to increase efficiency and accuracy in financial management, while overcoming various problems that arise due to changes in technology and policy. With the right approach, school financial administration can contribute significantly to improving the quality of education and public trust.